Effect of pH dynamic control on ethanol-lactic type fermentation (ELTF) performance of glucose - Yue, Liu (Environmental technology, 2022)
This study proposed a new ethanol-lactic type fermentation (ELTF) and explored the optimal control strategy. Using batch experiments, the effects of pH, temperature and organic loading (OL) on ELTF were investigated. The sum of ethanol and lactic acid yield was highest at whole-control pH value of 4.0, 35°C temperature and OL of 33 gCOD/L. To improve ELTF, the dynamic pH control in the long-term CSTR was adjusted at 4.0 (1-28 days), 5.0 (29-44 days) and 4.0 (46-62 days) successively. The high concentration of ethanol and lactic acid was 8190.5 mg/L at 16th day of pH 4.0. At pH of 5.0, the average acidogenesis rate and total concentration of fermentation products increased 111.0% and 128.0%, respectively. Organisms of Lactobacillus and Bifidobacterium were the predominant bacteria in reactor. It can achieve the directional regulation of ELTF and provides parameter support for the application of two-phase anaerobic digestion